A simple walking control method for biped robot with stable gait - Phuong, Nguyen Thanh; Huy, Tran Dinh; Cuong, Ngo Cao; Loc, Ho Dac (Journal of Computer Science and Cybernetics, 2013)
This paper proposes asimple walking control method for a 10 degree of freedom (DOF) biped robot with stable and human-like walking using simple hardware configuration. The biped robot is modeled as a 3D inverted pendulum. A walking pattern is generated based on ZMP tracking control systems, which are constructed to track the ZMP of the biped robot to zigzag ZMP reference trajectory decided by the footprint of the biped robot. An optimal tracking controller is designed to control the ZMP tracking control system. When the ZMP of the biped robot is controlled to track the x and y, ZMP reference trajectories always locates the ZMP of the biped robot inside stable region known as area of the footprint, a trajectory of the COM is generated as a stable walking pattern of the biped robot. Based on the stable walking pattern of the biped robot, a stable walking control method of the biped robot is proposed by using the inverse kinematics.The stable walking control method of the biped robot is implemented by simple hardware using PIC18F4431 and dsPIC30F6014. The simulation and experimental results show the effectiveness of the proposed control method.